2015
DOI: 10.1016/j.ccell.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The Inositol Polyphosphate 5-Phosphatase PIPP Regulates AKT1-Dependent Breast Cancer Growth and Metastasis

Abstract: Metastasis is the major cause of breast cancer mortality. Phosphoinositide 3-kinase (PI3K) generated PtdIns(3,4,5)P3 activates AKT, which promotes breast cancer cell proliferation and regulates migration. To date, none of the inositol polyphosphate 5-phosphatases that inhibit PI3K/AKT signaling have been reported as tumor suppressors in breast cancer. Here, we show depletion of the inositol polyphosphate 5-phosphatase PIPP (INPP5J) increases breast cancer cell transformation, but reduces cell migration and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 55 publications
3
106
0
Order By: Relevance
“…The use of protein domains for the detection of phosphoinositides as biosensors has been reported in previous studies (Davies et al, 2014;Ooms et al, 2015). Fluorescence intensity has been determined in N1 vector control cells or N1shSHIP2 cells transfected with GFP-PH-PLCδ1, used as a probe for PI(4,5)P2 (Stauffer et al, 1998).…”
Section: Lowering Ship2 Expression Potentiated Cell Migration In N1 Gmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of protein domains for the detection of phosphoinositides as biosensors has been reported in previous studies (Davies et al, 2014;Ooms et al, 2015). Fluorescence intensity has been determined in N1 vector control cells or N1shSHIP2 cells transfected with GFP-PH-PLCδ1, used as a probe for PI(4,5)P2 (Stauffer et al, 1998).…”
Section: Lowering Ship2 Expression Potentiated Cell Migration In N1 Gmentioning
confidence: 98%
“…In breast cancer cells, the inositol polyphosphate 5-phosphatase synaptojanin 2 promotes cell migration and invasion in culture but also lung metastasis of breast tumor xenografts in mice (Ben-Chetrit et al, 2015). In another study, depletion of the proline-rich inositol polyphosphate 5-phosphatase PIPP (also known as INPP5J) has been shown to increase transformation and accelerate oncogene-driven tumor growth in vivo, whereas paradoxically reducing cell migration, invasion and metastasis (Ooms et al, 2015); this study identifies PIPP as a suppressor of oncogenic PI3K signaling in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive efforts have been made towards a better understanding of human breast cancer oncogenic events, and many biomarkers have been reported to be an indicator for initiation and invasion of breast cancer. These may include among others; proline rich inositol polyphosphate 5-phosphatase (PIPP), which when depleted inhibits PI3K/AKT signaling, enhanced the transformation ability of breast cancer cells, but reduced cell migration and invasion thus indicating that PIPP is a potential suppressor of oncogenic PI3K/AKT signaling in breast cancer (8); bone marrow stromal antigen 2 which is expressed in cancer cells and facilitates the emergence of neoplasia and malignant progression of breast cancer (9) and others such as oncoprotein hepatitis B X-interacting protein which when mediated by general control non-derepressible 5 promotes the migration of breast cancer cells and therapeutically could act as a novel target in breast cancer (10).…”
Section: Introductionmentioning
confidence: 99%
“…Overactivation of AKT signaling can also induce the upregulation of NFATC1 and further promote osteoclastogenesis [36]. At the same time, overactivation of AKT can also promote tumor proliferation and migration [35,37,38]. Our results indicated that GCTSC-secreted CCL20 could significantly induce the overactivation of both the AKT and NF-κB pathways during osteoclast differentiation.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 69%